ON THE PROBLEMS OF TRAINING SCIENTIFIC PERSONNEL OF THE HIGHEST QUALIFICATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article briefly discusses some historical facts from the preparation of candidates of sciences at the ISU. K. Tynystanova. The authors indicate the directions of entry of young researchers into the scientific field of activity. In this case, in order to participate in the scientific community, young teachers need to get a recommendation from the State Certification Commission to apply for a master’s degree and then a postgraduate degree. Many changes are creating new problems by tightening previous requirements. Specific problems in the preparation of highly qualified scientific and pedagogical personnel are identified and possible ways to solve them are outlined.
Keywords: multilevel training of specialists, research activities, postgraduate study, supervisor, academic degree, publication of articles, plagiarism, dissertation submission.